Attraverso il corpo. Donne di una bidonville di Haiti e doni dello sviluppo - Pia Maria Koller (EtnoAntropologia)
Living in Cité Soleil, the largest haitian slum, is in itself a stigma, hindering access to social services and humanitarian aid. Repression and the increasing presence of armed gangs imposed a culture of silence. Violence became normality, particularly against women. Their survival strategies can be summarized by kalkile, calculate, pervading the individual and social body. When confronted with inequity in health, choices may turn into acts of resistance.